Changes in forest cover in Sierra Nevada, Mexico, 1994–2015. Issue 2 (3rd July 2019) - López-García, José
ABSTRACT: Sierra Nevada, 153, 437 ha, has the second and third highest mountains in Mexico and the most conserved coniferous forests of central Mexico. It comprises the Los Volcanes Biosphere Reserve, designated by UNESCO in 2010. A map was produced at 1:100, 000 scale. Recent changes in forest cover were identified by visual interpretation of orthophotographs from 1994 and Spot 7 images from 2015. Changes were detected in forest cover density (closed, semi-closed, semi-open, open or deforested), together with a non-forest category that includes other land uses. Over the 21 years, 25% of the forest had undergone change: 14% recovery and 11% disturbance. Recovery outweighed disturbance in the Protected Areas, with possible factors being payment for environmental services, periodic reforestation and fire control. Outside this protected area, improvement outweighed degradation, mainly because of forestry programs. Overall in the Sierra Nevada, the trend appears to be forest recovery.